A NEW TECHNOLOGY IN SERVICE MARKETING CONSUMER SATISFACTION IN DETERMINING USE OF SERVICES - Dwi Yuda Syaputra (Jurnal Ekonomi, 2022)
This research was conducted in the J&T Mongons branch in Medan where this study aims to find out how the influence of the service marketing mix consists of Product (X1), Promotion (X2), Price (X3), Location (X4), People (X5), Evidence Physical (X6), and Process (X7) on Consumer Purchasing Decisions (Y) to use J&T expedition services, Mongonsidi Medan Branch. The population in this study was 375 consumers with a sample size of 79 samples. The sample size is determined by the Slovin formula with an error tolerance of 10%. The research was conducted from June to October 2019. This research used quantitative data that was processed using the SPSS application with a multiple linear regression model. The data source used is primary data taken directly from the respondents. The results of the study show that product, promotion, price, location, people, physical evidence, and process have a positive and significant influence both partially and simultaneously on purchasing decisions to use J&T expedition services, Mongonsidi Branch in Medan. Process variables are the variables that most influence consumer purchasing decisions. Products, promotions, prices, locations, people and physical evidence, and processes contribute 88.0% to the formation of consumer purchasing decisions. Products, promotions, prices, locations, people and physical evidence, and processes have a very strong relationship to consumer purchasing decisions.